2017
DOI: 10.1371/journal.pone.0179016
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum ferritin level on overall survival in patients with myelodysplastic syndromes: Results of a meta-analysis of observational studies

Abstract: BackgroundThe role of serum ferritin (SF) as a prognostic factor has been analyzed in patients with myelodysplastic syndromes (MDS) who have undergone hematopoietic stem cell transplantation (HSCT), but the prognostic role of elevated SF levels is still controversial in lower risk MDS patients. Therefore, we performed a meta-analysis of all available published literature to evaluate whether elevated SF levels are associated with a worse overall survival (OS) among patients with low risk MDS.Material and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…These results showed that the expression of ferritin is positively correlated with tumor growth. As mentioned above, recent studies revealed that the higher ferritin expression in malignant tumors is related to myelodysplastic syndromes [14], cancer metastasis [15] [16], drug resistance [5] [6], and poor prognosis [17]. The higher ferritin expression determined in our study makes further investigations necessary to elucidate the function of ferritin in different compartments of cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…These results showed that the expression of ferritin is positively correlated with tumor growth. As mentioned above, recent studies revealed that the higher ferritin expression in malignant tumors is related to myelodysplastic syndromes [14], cancer metastasis [15] [16], drug resistance [5] [6], and poor prognosis [17]. The higher ferritin expression determined in our study makes further investigations necessary to elucidate the function of ferritin in different compartments of cancer cells.…”
Section: Discussionsupporting
confidence: 53%
“…This survival advantage remained after matched pair analysis adjusting for age, frailty, comorbidity and R‐IPSS. However, there are no randomized prospective studies demonstrating superior outcomes with iron chelation therapy and there is controversial data with regard to the serum ferritin threshold which should trigger chelation . The NCCN guidelines recommend the use of chelation therapy in patients with ferritin levels above 2500 ng/mL .…”
Section: Risk Adapted Therapymentioning
confidence: 99%
“…During the early 10 years, numerous studies have shown that elevated SF prior to HSCT is detrimental to OS with an increase in nonrelapse mortality, as a consequence of iron overload toxicity [6][7][8][9][10]. However, the enrollments in many previous articles always included various diseases, including AA, myelodysplastic syndromes, and acute or chronic hematologic malignancies [3,11,12]. As it is still unknown whether SF plays the same role in different hematologic diseases, and patients with those different kinds of diseases also received different amounts of RBC transfusion, we enrolled only SAA patients this time.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous studies that have revealed the association between iron overload and allogeneic hematopoietic stem cell transplantation (allo-HSCT), and most investigators preferred serum ferritin (SF) as an indicator of iron burden, as well as an acute phase reactant [1]. However, controversies still exist over whether high-ferritin equals iron overload, and whether it leads to poor outcome [3].…”
Section: Introductionmentioning
confidence: 99%